Potential of silicon nutrient in reducing fungal disease in red-fleshed dragon fruit - Nurul Faziha I.,; Muhammad Ariff M.R.,; Fahim N.A.,; Mohamad Naziem Ezzry P.,; Suhaizan L., (Penerbit Universiti Kebangsaan Malaysia, 2019)
Dragon fruit has a high market value and widely cultivated in Malaysia. Nowadays, the dragon fruit plants are severely infected by fungal diseases causing economic loss to many farmers. This study was carried out to evaluate the potential of silicon treatments in reducing disease incidence and disease severity in dragon fruit plants. For this purpose, three silicon concentrations namely 1.5, 2.5 and 5.0 ml/L were applied as root treatment. Control plant was only irrigated with tap water. Occurrence of disease incidence and disease severity were recorded starting from planting until harvesting period and was later calculated. After harvest, silicon accumulation in both stems and fruits was determined using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Based on the results, plants treated with T3 showed lower disease incidence and disease severity as compared to the other treatments and control. Average silicon accumulations in stems ranged between 28.10 ppm to 42.22 ppm, and between 110.59 ppm to 198.28 ppm in the fruits. A substantial response has been observed on uptake of silicon in reducing disease severity in dragon fruit plants. Thus, application of silicon nutrient could help to improve plant defence mechanism in many agricultural crops, which could become a good strategy in controlling the diseases.